Literature Review on Behaviour Accounting in University - Masitah, Dewi; Armiani, Armiani (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to analyze the development of accounting Behaviour during the 2019-2024 period. The method used is Systematic Literature Review (SLR), which is a technique for identifying, disseminating and interpreting all relevant and available research. The population and sample in this study consisted of 35 journals that discussed articles regarding Behavioural accounting in universities as non-profit organizations in the period 2019-2024. The results of this literature review can be used as a reference for further research, with a classification of accounting topics that discuss fraud as part of internal control. The classification of research methods used is surveys or questionnaires, while the classification based on research subjects is students who act as respondents in the research. It is hoped that the results of this literature reflection can become the basis for subsequent research or research with a focus on accounting topics related to fraud as internal control, using research methods in the form of surveys or questionnaires, and involving students as subjects or respondents in research.